2018
DOI: 10.15406/mojcrr.2018.01.00020
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute lower respiratory tract infection: a study in hospitallized central Indian children under 5 year age

Abstract: Background and aim: Preventive measures of regional relevance can be conceived based on understanding of predominant risk factors. Present observational study endeavored collection of evidence on hierarchy of risk factors for acute lower respiratory infection (ALRI), in under 5 year age children hospitalized in a city in central India. Method: A transactional case control observational study was carried out in 100 hospitalized under 5 year age children of ALRI and 100 healthy babies of similar age and sex comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
1
0
3
Order By: Relevance
“…Low birth weight in term infants is a surrogate marker of intrauterine growth restriction. 9 This presents a high risk of ARI due to structural deformation that endangers lung health and impaired immune competence. The same study was also conducted by other research who said the effect of LBW on ARI showed significant results, namely with a p-value of 0.04 with an RR value of 1.15 times (95% CI 1.00 -1.31) which means that children under five years with LBW are at risk 1.15 times to experience ARI when compared to children under five years with normal birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Low birth weight in term infants is a surrogate marker of intrauterine growth restriction. 9 This presents a high risk of ARI due to structural deformation that endangers lung health and impaired immune competence. The same study was also conducted by other research who said the effect of LBW on ARI showed significant results, namely with a p-value of 0.04 with an RR value of 1.15 times (95% CI 1.00 -1.31) which means that children under five years with LBW are at risk 1.15 times to experience ARI when compared to children under five years with normal birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Ke delapan belas artikel yang telah di-review, terdapat berturut-turut 7, 4, 4, 6, dan 6 artikel yang membahas keterkaitan faktor fisiologis usia, BBLR, status gizi, ASI eksklusif, dan jenis kelamin dengan kejadian ISPA pada balita. Secara detail terdapat tiga artikel yang mengulas adanya pengaruh dari keempat kombinasi faktor risiko fisiologis (Anteneh & Hassen, 2020;Deepti & Abha, 2018;Nguyen et al, 2019;Taksande & Yeole, 2016). Penelitian Sultana et al (2019) dan Ullah et al (2019) mengatakan usia balita kurang dari 12 bulan dan jenis kelamin pria lebih berisiko tinggi terkena ISPA.…”
Section: Gambar 1 Diagram Alur Tahapan Tinjauan Kepustakaanunclassified
“…Balita dengan BBLR umumnya mengalami hambatan pertumbuhan selama di dalam kandungan. Menurut penelitian Deepti & Abha (2018) hal ini menjadi salah satu penyebab terjadinya deformasi dari sturuktural paru pada calon bayi. Pendapat ini memperkuat laporan Ronkainen et al (2016) yang menduga terjadi pembatasan pertumbuhan intra-uterus pada balita BBLR sehingga timbul kelainan struktur dan fungsi paru.…”
Section: Pengaruh Berat Badan Lahir Rendah Terhadap Kejadian Ispaunclassified
See 1 more Smart Citation